The Influence of Tri-Nga Integrated Deep Learning Approach on Students' Conceptual Understanding and Learning Motivation (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Education is a conscious and planned process to create a learning atmosphere and learning process so that students actively develop their potential, both in terms of intellectual, spiritual, social, and skills, so that they become individuals with character and are able to contribute to community life. This study aims to test the hypothesis of the effect of the Tri-Nga integrated Deep learning approach on the understanding of concepts and learning motivation of fifth grade students in Mathematics Education. The population of this study was all fifth grade students at SD Kalikotes District, Klaten Regency which consists of 6 schools. The number of fifth grade students is 243 students. The type of research used by the researcher is quasi-experimental research or pseudo-experiment. The data collection technique used is observation and pretest posttest in the form of multiple choice to measure conceptual understanding and essay questions to measure student learning motivation. The data analysis technique used in this study is descriptive analysis and statistical analysis. The results of this study concluded that the data obtained from the analysis using the Manova test, showed that there was a significant difference in the ability to understand concepts and learning motivation of fifth grade students in Mathematics after the implementation of the Tri-Nga integrated Deep Learning teachings approach. This is indicated by the Hotelling's Trace significance value of 0.007 for conceptual understanding and 0.000 for learning motivation, both of which are below the significance level of 0.05. Students who follow learning with this approach show better conceptual understanding and higher learning motivation than students who do not use it. This increase occurs because the Tri-Nga integrated Deep Learning approach is able to encourage students to understand the material in depth (ngerti), feel the meaning of learning (ngrasa), and apply it in real life (nglakoni), so that they become more active, motivated, and easy to solve learning problems.